If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.1(5x + -7) + 3.6 = 0.2(9 + -2x) Reorder the terms: 1.1(-7 + 5x) + 3.6 = 0.2(9 + -2x) (-7 * 1.1 + 5x * 1.1) + 3.6 = 0.2(9 + -2x) (-7.7 + 5.5x) + 3.6 = 0.2(9 + -2x) Reorder the terms: -7.7 + 3.6 + 5.5x = 0.2(9 + -2x) Combine like terms: -7.7 + 3.6 = -4.1 -4.1 + 5.5x = 0.2(9 + -2x) -4.1 + 5.5x = (9 * 0.2 + -2x * 0.2) -4.1 + 5.5x = (1.8 + -0.4x) Solving -4.1 + 5.5x = 1.8 + -0.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.4x' to each side of the equation. -4.1 + 5.5x + 0.4x = 1.8 + -0.4x + 0.4x Combine like terms: 5.5x + 0.4x = 5.9x -4.1 + 5.9x = 1.8 + -0.4x + 0.4x Combine like terms: -0.4x + 0.4x = 0.0 -4.1 + 5.9x = 1.8 + 0.0 -4.1 + 5.9x = 1.8 Add '4.1' to each side of the equation. -4.1 + 4.1 + 5.9x = 1.8 + 4.1 Combine like terms: -4.1 + 4.1 = 0.0 0.0 + 5.9x = 1.8 + 4.1 5.9x = 1.8 + 4.1 Combine like terms: 1.8 + 4.1 = 5.9 5.9x = 5.9 Divide each side by '5.9'. x = 1 Simplifying x = 1
| 2x(m+5)=40 | | .05x+1.5-.10x=1.15 | | 0.8x(4x-3)+0.3(7-10x)=-0.2 | | 4x-3y=-32 | | 3(x+10)-3=81-3x | | f(x)=((4))/((3x^2-5x^4)^4) | | 9x-4=158 | | [7x+4]+9=4 | | 0.5x-0.4x(3x+8)=0.3 | | (4)/((3x^2)-(5x^4))^4 | | 3y+2(y-4)=2 | | (11((x-7)/2)^2)-20=101 | | 15/9=8/5 | | (4)/((3x^2-5x^4)^4) | | 3x+13=90 | | ((4)/((3x^2-5x^4)^4)) | | f(x)=(4)/(3x^2-5x^4)^4 | | 9x-4=39.5 | | (4)/(3x^2-5x^4)^4 | | -10-m=-70 | | 36=(90/360)*x*x | | 4a-14=2a | | (4/5)-(2x/3)=(3/10) | | (x-3)(x+1)=x*-11 | | n^3-64/125 | | 3m-1-36=11 | | 3.16x+x= | | (X-3)(x+1)=x*11 | | 5n-7=32 | | m-39+93-13=36 | | log(22/x) | | x-.1=18000 |